Strategy for Development of Rice Sawah Culture Planting in Jarwo Plants with Various Modification of Plant Distance - Paulina, Utami; Syarif, Auzar; Anwar, Aswaldi; Anwar, Aswaldi (International Journal of Environment, Agriculture and Biotechnology, 2020)
Rice is the main food crop of the Indonesian population, mostly planted in paddy fields. The speed of population growth is not balanced with a decrease in rice production that occurs due to a decrease in harvested area. This research aims to determine the interaction between distance planting in the jarwo planting system on the growth and yields of lowland rice (oryza sativa). This research was conducted in December 2018 until March 2019 in Andalas Makmur, Parak Karakah, Kuranji District, Padang. The method used was a Randomized Block Design (RBD) with 2 factors governing spacing, consisting of 3 levels, namely J1: Distance planting (20 x 25) cm², J2: Planting distance (25x 25) cm², J3: Planting distance (30 x 25) cm², The second factor of the jarwo planting system consists of 4 levels, namely L1: Jajarlegowo 2: 1, L2 : Jajarlegowo 3: 1 A, L3: Jajarlegowo 3: 1 B, L4: Jajarlegowo 4: 1. In this experiment there were 12 combinations. Each combination consists of 3 groups. The observational data were statistically analyzed by the F test and if the F test count was greater than the F table of 5%, then continued with Duncan's New Multiple Range Test (DNMRT) at the 5% significance level. The results showed that there was no interaction between planting distances in various jarwo planting systems on growth and yields of paddy (oryza sativa).